Respuesta :

Cxlver

d(x) = 2x -6

[tex]d(d^{-1}(x)) =  x = 2d^{-1}(x) - 6 => d^{-1}(x) = \frac{1}{2}x + 3[/tex]

Answer: [tex]d(x)^{-1}=-\frac{x}{2}-3[/tex]

Step-by-step explanation:

Rewrite the function with [tex]d(x)=y[/tex]

[tex]y=-2x-6[/tex]

Solve for the variable "x":

[tex]y=-2x-6\\\\y+2x=-6\\\\2x=-6-y\\\\x=\frac{-6-y}{2}[/tex]

Now exchange the variables:

[tex]y=\frac{-6-x}{2}[/tex]

Simplify. Then, the inverse function of [tex]d(x)=-2x-6[/tex] is:

[tex]d(x)^{-1}=-\frac{x}{2}-3[/tex]

ACCESS MORE